The impact of aging time on fracture mode of a metastable β alloy with network-like microstructure. (November 2021) - Shan, Di; Wang, Le; Fang, Changqing; Shao, Hui; Fan, Dan; Wang, Kaixuan; Yan, Guo
Highlights: Three-step heat treatment is proposed to obtain high strength and plasticity alloys. The fracture mode is evaluated from the composition and microstructure of the alloy. The fracture mode of the alloy changes with the change of aging time. Abstract: Metastable β alloys (Ti-5Al-2Sn-2Zr-4Cr-4Mo) with network-like microstructure were obtained by aging at 630 °C for 1–25 h, and subjected to the tensile fracture at room temperature. The obtained alloy (equiaxed α and precipitated α phases) has the high strength and good plasticity, which are comparable to those of near-β forged alloys. The tensile fracture mode of the short-time aging alloy is the ductile fracture with local long voids. The micro-cracks initiation at the grain boundary α layer and adjacent equiaxed α phases gives rise to the long voids. As the aging time increases up to 25 h, Al atoms penetrate within equiaxed α phase and Mo atoms pile up along the α/β interface. During the tensile process, the release of local stress is due to the α/β interface softening. The ductile fracture of the long-time aging alloy is determined by the void growth and coarsening.